The moderating effect of family business ownership on the relationship between short-selling mechanism and firm value for listed companies in China - Wenzhen Mai; Nik Intan Norhan Bt Abdul Hamid (Journal of Risk and Financial Management, 2021)
This study demonstrates an investigation of the external corporate governance effect of short selling mechanisms on firm value in the Chinese context. The effect of family businesses is also examined as a moderator of the relationship between short-selling and firm value. Using panel data analysis of Chinese listed companies, this paper tests a total sample of 22,468 firm-year observations from the Shanghai and Shenzhen Stock Exchange from 2009 to 2019 by applying the PSM-DID method in order to mitigate self-selection and endogenous problems caused by the uniqueness of Chinese short selling mechanisms. The findings suggest that both deregulation and the propensity of short selling can improve the firm value. Our findings also established that family ownership weakens firm value with the availability of short-selling, which indicates that family businesses have long orientations and conduct better corporate governance practices than non-family business, as short-selling shows a weaker external governance effect on firm value creation by family businesses in China. A robust test of alternative measurements is conducted and validated. This study provides significant insights for policymakers to consider in order to further relax short-selling constraints, which can act as effective external governance for better firm value creation, especially for non-family businesses in developing countries.
Keywords: 330; family ownership; firm value; short-selling